Instructional Media Big Book Literacy Based Indonesian Narrative Text to Improve Elementary School Students’ Reading Comprehension Skills - I Wayan Elsiyana; Maria Goreti Rini Kristiantari; Basilius Redan Werang (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low reading skills of elementary school students, especially in understanding narrative texts. The purpose of this study is to develop a Big Book learning media based on Indonesian narrative text literacy that is effective in improving the reading skills of fourth grade elementary school students. The development model used is the ADDIE model ((analyze, design, development, implementation and evaluation). The subjects of the study were 25 fourth grade students. Data collection methods include observation, interviews, questionnaires, and reading skills tests. The instruments used are expert validation questionnaire sheets, and reading evaluation questions. The data analysis techniques used are qualitative and quantitative descriptive analysis. The results of the study showed tcount (24.59) > ttable (1.711) so that H0 was rejected and H1 was accepted. So it can be concluded that literacy-based big book learning media is effective to be applied to Indonesian narrative texts to improve reading comprehension skills in fourth grade elementary school students. The implications of this study show the importance of using contextual and attractive visual media to support literacy learning in elementary schools.